Depression and anxiety symptoms among Afghan war widows and their associated factors: A cross-sectional analytical study - Naqib Ahmad Dost; Muhammad Haroon Stanikzai; Massoma Jafari (Indian Journal of Psychiatry)
Background: The 4 decades of conflict have particularly exacerbated the mental health of Afghan war widows, a population that has not been extensively studied in this context. Aim: This study aims to fill the gap in the literature by providing robust data on the prevalence of depression and anxiety symptoms and identifying associated factors among Afghan war widows. Methods: A cross-sectional study was carried out in 2023, interviewing war widows from four community health centers in Kandahar, Afghanistan. We employed a validated Patient Health Questionnaire and Generalized Anxiety Disorder Scale. A multivariable binary logistic regression model was used to determine factors associated with depression and anxiety symptoms. Results: The prevalence of depression and anxiety symptoms was 57.9% (95% CI: 52.7%–62.8%) and 61.5% (95% CI: 56.4%–66.4%), respectively. There were significant differences in the prevalence of mental health symptoms across our population with different sociodemographic and health-related profiles (in particular, time since widowhood, household income, history of comorbidity, and level of social support). Conclusion: The stark prevalence of mental health issues among Afghan war widows underscores an overlooked humanitarian crisis. The findings call for immediate mental health interventions, tailored to the sociopolitical realities of Afghanistan.